Pembekalan Wirausaha Pemasaran Mandiri Bagi UMKM Makanan Tradisional Rengginang Di Jl. RE Martadinata RT.12 RW.02 NO.15 Kel. Kandang Mas Kec. Kampung Melayu Kota Bengkulu - Wagini, Wagini; Dila, Viana; Fitri, Henny Desfijar; Yulianti, Oni; Harwini, Dewi (Jurnal Dehasen Mengabdi, 2022)
MSMEs are one of the growing economic sectors in Indonesia. This sector is mostly run by entrepreneurs because it is easy to manage and does not require too large a cost in the process of its establishment. One of the MSMEs that are often found in the city of Bengkulu is MSMEs that produce and sell food made from black sticky rice. This community service activity will be held on Jl. RE Martadinata RT.12 RW.02 NO.15 Kel. Cage Mas Kec. Bengkulu City Malay Village. With this socialization, MSMEs still sell products in the form of Rengginang Ketan Hitam in conventional ways that do not yet have good product characteristics or brand image for consumers. As well as making MSMEs aware of the importance of using product names/brands so that they are easily recognized by consumers. The socialization of entrepreneurship carried out in this service is carried out in several stages, the first stage of awareness, the second stage of capacity building and stages of empowerment. all stages have been practiced for MSME actors at RT.12 RW.02 NO.15 Kel. Kandang Mas Kec. Kampung Melayu Bengkulu City and can be received with a fairly high enthusiasm. After this socialization is carried out, MSME actors can create brands and sell products to the market and use current technology. It is hoped that every MSME can create product characteristics or brands to be easily recognized by consumers and help increase product sales.